EPSA11 perspectives and foundational problems in philosophy of science - Dieks, Dennis (The European Philosophy of Science Association Proceedings, 2013)
This book contains a selection of original conference papers covering all major fields in the philosophy of science, that have been organized into themes. The first section of this volume begins with the formal philosophy of science, moves on to idealization, representation and explanation and then finishes with realism, anti-realism and special science laws. The second section covers the philosophy of the physical sciences, looking at quantum mechanics, spontaneous symmetry breaking, the philosophy of space and time, linking physics and metaphysics and the philosophy of chemistry. Further themed sections cover the philosophies of the life sciences, the cognitive sciences and the social sciences. Readers will find that this volume provides an excellent overview of the state of the art in the philosophy of science, as practiced in different European countries.